Awareness, Attitudes And Perceptions Of Drive-Thru Community Pharmacy Service During Covid-19 Among Community Pharmacists And General Public In Malaysia: A Mixed Methods Study - Ababneh, Bayan Faisal Abdul Kareem (2024)
There is a lack of attention to drive-thru services in the community pharmacy setting, particularly during the COVID-19 period in Malaysia. Previous studies focused on the drive-thru pharmacy services limited to the government hospitals or before COVID-19. To effectively assess the drive-thru community pharmacy service during COVID-19 in Malaysia, it is essential to explore the perceptions of service providers (community pharmacists) and the general public towards this service. Mixed methods techniques (qualitative and quantitative) were used in this research work. In the qualitative phase, semi-structured interviews were conducted among 25 community pharmacists. Thematic analysis of the qualitative study yielded seven major themes as follows: 1-familiarity with drive-thru community pharmacy service during COVID-19, 2-willingness toward this service during COVID-19, 3-perceived benefits toward drive-thru community pharmacy service during COVID-19, 4-perceived disadvantages toward this service, 5-barriers toward drive-thru community pharmacy service, 6-factors affecting the preference toward this service, and 7-facilitators to drive-thru community pharmacy service. The major findings from the qualitative part of this research work are that community pharmacists reported positive attitudes toward drive-thru community pharmacy service during COVID-19. However, concerns about poor communication between the pharmacist and the patient, limited counseling, and dispensing errors were acknowledged.